Safety and effectiveness of underwater cold snare resection without submucosal injection of large non-pedunculated colorectal lesions - Yen, Andrew W.; Leung, Joseph W.; Koo, Malcom; Leung, Felix W. (Endoscopy International Open, 2022)
Background and study aims Adverse events are uncommon with cold snaring, but cold techniques are generally reserved for lesions ≤ 9 mm out of concern for incomplete resection or inability to mechanically resect larger lesions. In a non-distended, water-filled lumen, colorectal lesions are not stretched, enabling capture and en bloc resection of large lesions. We assessed the effectiveness and safety of underwater cold snare resection (UCSR) without submucosal injection (SI) of ≥ 10 mm non-pedunculated, non-bulky (≤ 5 mm elevation) lesions with small, thin wire snares.Patients and methods Retrospective analysis of an observational cohort of lesions removed by UCSR during colonoscopy. A single endoscopist performed procedures using a small thin wire (9-mm diameter) cold or (10-mm diameter) hybrid snare.Results Fifty-three lesions (mean 15.8 mm [SD 6.9]; range 10–35 mm) were removed by UCSR from 44 patients. Compared to a historical cohort, significantly more lesions were resected en bloc by UCSR (84.9 % [45/53]; P = 0.04) compared to conventional endoscopic mucosal resection (EMR) (64.0 % [32/50]). Results were driven by high en bloc resection rates for 10– to 19-mm lesions (97.3 % [36/37]; P = 0.01). Multiple logistic regression analysis adjusted for potential confounders showed en bloc resection was significantly associated with UCSR compared to conventional EMR (OR 3.47, P = 0.027). Omission of SI and forgoing prophylactic clipping of post-resection sites did not result in adverse outcomes.Conclusions UCSR of ≥ 10 mm non-pedunculated, non-bulky colorectal lesions is feasible with high en bloc resection rates without adverse outcomes. Omission of SI and prophylactic clipping decreased resource utilization with economic benefits. UCSR deserves further evaluation in a prospective comparative study.